2000
DOI: 10.1103/physrevb.62.13595
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the luminescence spectra of InAs self-assembled quantum dots by resonant tunneling through a quantum well

Abstract: We investigate carrier dynamics in optically excited n-i-n GaAs/(AlGa)As resonant tunneling diodes that incorporate a single layer of InAs quantum dots in the center of the GaAs quantum well (QW). Voltage-tunable resonant changes in the dot luminescence are observed and are discussed in terms of the tunneling of carriers into the resonant states of the QW and of the capture of carriers from the QW into the dots

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 13 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…In dark condition, we have observed only one electron resonant peak which was associated to the resonant tunneling through the second confined level e2 in the QW. It was shown previously [8] that even when QDs are formed, a wetting layer is still present and changes the position of the first QW confined level (e1) to a new position below the GaAs conduction-band. Therefore, resonant tunneling through e1 states cannot be observed in the I(V) characteristics curve.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In dark condition, we have observed only one electron resonant peak which was associated to the resonant tunneling through the second confined level e2 in the QW. It was shown previously [8] that even when QDs are formed, a wetting layer is still present and changes the position of the first QW confined level (e1) to a new position below the GaAs conduction-band. Therefore, resonant tunneling through e1 states cannot be observed in the I(V) characteristics curve.…”
Section: Resultsmentioning
confidence: 99%
“…Under light excitation, holes are photocreated in contact layer region and tunnel through the double barrier structure. An additional resonant peak associated to hh2 hole resonance [8] is observed in lower voltage region under higher laser intensities. We have also observed that the photocurrent rapidly increases at low voltages (0.2 V), saturates in the region of about 0.2 and 0.4 V, and eventually follows the similar resonant voltage dependence as the current measured in dark conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as we adjust the voltage we can study different energy states of the QDs. At sufficiently high voltages we are able to observe two separate resonances in the current related to confined subbands of the QW states [11]. Figure 2 shows a typical low-temperature (T ¼ 4.2 K) I(V) curve in reverse bias (positive-biased substrate).…”
mentioning
confidence: 96%
“…The layer of InAs QDs was grown by depositing 2.3 monolayers (ML) of InAs. Undoped GaAs spacer layers of width 50 nm separate the barriers from two contact layers with graded n-type doping [38]. The device acts as a resonant tunnelling diode in which electrons can tunnel into the QD from a doped contact layer on the opposite side of the barrier.…”
Section: Effects Of Growth Interruptionmentioning
confidence: 99%